Frequency of Low Birth Weight Neonates in Mothers with Low Serum Ferritin Levels: Frequency of Low Birth Weight Neonates in Mothers - Khan, Samra; Baloch, Falak Naz; Bosan, Rabia; Khan, Aiman; Khan, Muneeba; Punar, Zakir Ali; Munaf, Zobia (Pakistan Journal of Health Sciences, 2025)
Birthweight significantly influences health throughout life, but the connection between maternal serum ferritin levels during pregnancy and the newborn’s birthweight is still a topic of debate. Objective: To investigate the prevalence of underweight infants born to the mothers with low blood ferritin concentrations at term delivery. Methods: A descriptive cross-sectional study was conducted for a period of six months from November 2019 to April 2020. A total of 151 participants with reduced serum ferritin concentrations at full-term delivery were included in this study. Demographic details were taken including blood sample for serum hemoglobin and ferritin levels were checked and noted in a questionnaire. Data stratification was performed to eliminate other effect modifiers and to statistically test the significance of low birth weight of neonates in mother with low serum ferritin levels, with the help of chi-square test. Results: The typical age of the patients was 25.50 ± 4.08 years. Incidence of Low Birth Weight newborn in mother with reduced serum ferritin levels at term delivery was observed in 33.11% (50/151). Conclusions: Low birth weight, a prevalent issue in Pakistan, is a significant contributor to perinatal morbidity and mortality. Correction of anemia, consuming a diet with a proper nutrient balance and accessing maternal care during pregnancy are anticipated to decrease the incidence of underweight infants and lower perinatal death rate. This study suggests that mothers should receive counselling on prevention of teenage marriages and pregnancies, maintaining a birth interval of 3 years, iron supplementation during pregnancy and avoiding consanguineous marriages.